Development of quizizz-based learning media on digestive system materials in class xi - Ayu Indah Lestari; Khairuna (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2022)
The development of technology and information encourages the creation of innovative, effective, and efficient use of learning media. The use of Quizizz web learning media has a positive impact on teachers and students. Teachers are facilitated with the help of using Quizizz from the many materials that already exist in the application. The purpose of this study was to determine the feasibility and practicality of using the Quizizz website media. This research was conducted at Karya Tani Private High School, Panai Hulu District. The subjects in this study were students of class XI which consisted of 30 students. This study uses Research and Development (R&D) research methods using a 4D model, namely define, design, develop and desseminate. The types of data obtained in this study are quantitative data and qualitative data. The data analysis technique used in this research is the feasibility analysis and the practicality of the Quizizz website learning media which is viewed from the aspect of validity. The results of the feasibility assessment study were obtained with a score of 92.66% on material validation and 92.5% on media validation. The practicality assessment obtained a score of 91.5% on the validation of the biology teacher and 92.52% of the student response. It can be concluded that the use of the Quizizz website-based learning media is feasible to be used as a learning medium at the school and is practically used by students and teachers.